A Photographic Atlas of Selected Regions of the Milky Way - Barnard, Edward Emerson (Cambridge : Cambridge University Press, 2011)
Edward Emerson Barnard's Photographic Atlas of Selected Regions of the Milky Way was originally published in two volumes in 1927. Together, these volumes contained a wealth of information, including photographic plates of the most interesting portions of the Milky Way, descriptive text, charts and data. Only 700 copies were printed, making the original edition a collector's item. Reproduced in print for the first time, this edition combines both volumes of Barnard's Atlas. It directly replicates Barnard's text, and contains high-resolution images of the original photographic plates and charts, reordered so that they can be seen together. It also includes a biography of Barnard and his work, a Foreword and Addendum by Gerald Orin Dobek describing the importance of the Atlas and additions to this volume, and a pull-out section with a mosaic of all 50 plates combined in a single panorama.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Astronomical photography